(2R, 3S)-Pinobanksin-3-cinnamate ameliorates photoreceptor degeneration in Pde6rd10 mice. (3rd July 2017) - Li, Yin; Li, Tuo; Li, Jia-Zhang; Wu, Qing-Song
Abstract: As an inherited disorder caused by initial death of rod photoreceptors, retinitis pigmentosa is currently untreatable and usually leads to partial or complete blindness. (2 R, 3 S )-Pinobanksin-3-cinnamate (PC) is a new flavonone isolated from the seed of Alpinia galanga Willd, and has been reported to exert neuroprotective effects by upregulating endogenous antioxidant enzymes. In this study, the anti-oxidative and neuroprotective activity of PC against photoreceptor apoptosis in rd10 mouse model of retinitis pigmentosa was explored. PC showed to produce significant improvement in histology and function in rd10 mice through reducing oxidative stress. For the first time, the protective effects of PC were demonstrated against retina degeneration in rd10 mice and our study provides scientific rationale on using PC as the supplementary treatment to the outer retina diseases, including retinitis pigmentosa, in which oxidative stress is thought to contribute to disease progression.